Optimising F1 in schools car design: using CFD simulation and wind tunnel testing for enhanced aerodynamic performance / M. H. Muhammad ... [et al.] - Muhammad, M. H.; Den, M. N. A. M.; Kasiran, R.; Ikhsan, N. (Smart Manufacturing Research Institute (SMRI), 2024)
F1 in Schools, a STEM competition for students, fosters collaborative design and manufacturing of the fastest miniature cars inspired by Formula 1 racing. To achieve the fastest car, the design must be optimised to reduce drag as much as possible. This paper focuses on optimising drag force, a key determinant of speed and stability. Through CFD simulations, various design iterations were evaluated. Each change was made based on targeting airflow obstructions and flow separation. A wind tunnel experiment was conducted to verify the results obtained through CFD. Results show that modifications significantly reduced drag force by 9.89%. Insights from this study underscore the importance of iterative design processes. Further enhancements could involve analysing pressure distribution and lift force to maximise thrust utilisation and improve race performance.